(untitled) (Asian Education Studies, 2018)
This study aim for analyze satisfaction Higher education service which is a form of servant performed by managers to stakeholders, based on Internal Quality Evaluation (EMI) result, from EMI achievement, set the Standard Operational Procedure and Work Instruction model, given the satisfaction of service is a very important part. The research method is correlation with the indicator consist of standard of Content, Process, Competence of graduates, Educator and educational staff, Facilities and infrastructure of Education, Management of Prodi, Financing, Assessment, Research and Community Service, then, from EMI standard, correlated with stakeholders’ satisfaction, with satisfaction level determined by category (a) satisfactory, if Expected Service/ES = Perceived Service (PS), (b) is not satisfactory when perceived service is lower than expectation (ES ≥ PS) and (c) very satisfying/happy when the service is perceived to exceed expectations (PS≥ES), and then performed data analysis. To define the model using several stages of the 4-D model include stages, definitions, design, development, and use or application. The result of correlation on study program A and study program B and Islamic education are different, for study program A is Competency Standard of Graduates (X3) with regression coefficient b3 = 0,076 and correlation coefficient R3 = 0,186, while study program B is Graduate Competency Standard (X3) with regression coefficient b3 = 0,138 with correlation coefficient R3 = 0,183, while indicator education according to government’s provision, which has correlation level at graduate level. The results of this research become the basis in determining SOP Model and Work Instruction, which then tested at universities studied, and in general the application of this model is in the category of Satisfactory.